Proposta de modelo aplicado à construção de diagnóstico de aderência aos princípios de gestão do sistema Toyota de produção - Azambuja, Rodrigo Rocha (Universidade do Vale do Rio do Sinos, 2008)
Today, innumerable Organizations have a major opportunity to enchant their customers continuously searching to reduce their costs, improving their quality levels, customer lead time and cycle time through the application of Lean management, called in the Occident by Lean Manufacturing. The production system principles originally developed by the lead automotive company called Toyota in Japan, leads the company to be more competitive and attend the market needs at that time. These Lean Manufacturing Technologies have been widely utilized and applied by numerous manufacturing companies worldwide with an impact in perform and profits. A lot of measuring tools as been created to measuring this efficiency, and also, tools and methods to manage this kind of technology. This Paper considers to present a model focused in Diagnosis of the level of lack regarding lean manufacturing management system, with the intention to present improvements in the form of current evaluation methods and increases the capacity of dia
Keywords: aderência; eficácia; sistema de gestão; gestão enxuta; effectiveness; management system; lean manufacturing; Engenharias